Modeling of Drying Processes of Dates (Phoenix, Arecaceae) with Oven or TGA and Microbiological Properties of Fresh and Dried Dates. (21st September 2020) - Ertekin, Özlem; İpek, Yeliz
ABSTRACT: Drying method, which is one of the oldest preservation methods, is important for preserving fruits. Date palm fruit is an important food in human nutrition due to some vitamins, minerals, sugar, phenolic components, and high fiber content. In the literature, date palm drying was not studied sufficiently in the aspect of mathematical modeling and the effect of drying process on the microbiological properties. In this novel study, date palm drying process was applied with four different temperatures of 50°C, 70°C, 90°C, and 110°C with two different drying techniques; drying with oven and drying with thermogravimetric analysis (TGA). Chemical changes in the date palm structure after drying at different temperatures were investigated with FTIR analysis. Fibrous structure of palm fruit is also exhibited with SEM analysis. On the other hand, microbiological studies were applied both for fresh and dried date palm to observe the drying process effect on the growth of different types of microorganisms. Consequently, drying time decreased with increasing drying temperature while the color of the dried date palm fruit became darker with increasing temperature. However, the chemical structure was not affected. Drying time of oven drying technique was longer than drying with TGA technique. The mathematical model of the drying temperature depending on drying time is calculated as D T = − 37, 58 ln t + 237, 74 for TG-DTA drying experiments and D T = − 3 × 10 − 5 t 2 − 0, 0218 t + 122, 5 for drying process with oven. In addition, the microbiological load has significantly decreased or disappeared with the drying process.